Extracellular Vesicles: The Landscape in the Progression, Diagnosis, and Treatment of Triple-Negative Breast Cancer - Dong, Menglu; Liu, Quan; Xu, Yi; Zhang, Qi (Frontiers in Cell and Developmental Biology, 2022)
Triple-negative breast cancer (TNBC) is a heterogeneous subtype of breast cancer (BC) with diverse biological behavior, high aggressiveness, and poor prognosis. Extracellular vesicles (EVs) are nano-sized membrane-bound vesicles secreted by nearly all cells, and are involved in physiological and pathological processes. EVs deliver multiple functional cargos into the extracellular space, including proteins, lipids, mRNAs, non-coding RNAs (ncRNAs), and DNA fragments. Emerging evidence confirms that EVs enable pro-oncogenic secretome delivering and trafficking for long-distance cell-to-cell communication in shaping the tumor microenvironment (TME). The transferred tumor-derived EVs modify the capability of invasive behavior and organ-specific metastasis in recipient cells. In addition, TNBC cell-derived EVs have been extensively investigated due to their promising potential as valuable biomarkers for diagnosis, monitoring, and treatment evaluation. Here, the present review will discuss the recent progress of EVs in TNBC growth, metastasis, immune regulation, as well as the potential in TNBC diagnosis and treatment application, hoping to decipher the advantages and challenges of EVs for combating TNBC.